Andrew Wyeth : looking out, looking in - Anderson, Nancy K.; Brock, Charles, 1959-; Wyeth, Andrew, 1917-2009; Anderson, Nancy K.; Brock, Charles, 1959-; National Gallery of Art (U.S.) (Washington : National Gallery of Art, 2014)
"One of Andrew Wyeth's most important paintings, Wind from the Sea (1947), is also the artist's first full realization of the window as a recurring subject in his art. Wyeth returned to windows again and again during the next six decades, producing more than 300 remarkable works that explore the formal and conceptual aspects of looking both in and out of windows. Spare, elegant, and abstract, these non-figural paintings are free of the narrative element inevitably associated with his well-known compositions. This richly illustrated book presents a select group of Wyeth's tempera paintings--many of them never before published or on public view--along with two essays that explore Wyeth's fascination with windows." -- Publisher's website.
Introduction / Nancy K. Anderson and Charles Brock -- Wind from the sea : painting truth beneath the facts / Nancy K. Anderson -- Through a glass : the window in the art of Andrew Wyeth, Charles Sheeler, and Edward Hopper / Charles Brock -- Plates. Olson House Kuerner Farm Brandywine Studio Variations.
Issued in connection with an exhibition held at the National Gallery of Art, Washington, May 4-November 30, 2014.
Includes bibliographical references (pages 184-188) and index.
Keywords: Wyeth, Andrew, -- 1917-2009 -- Exhibitions; Windows in art -- Exhibitions